The Unconscious Mind Worry: A Mechanistic-Explanatory Strategy. Issue 1 (22nd January 2023) - Krickel, Beate
Abstract: Recent findings in different areas of psychology and cognitive science have brought the unconscious mind back to center stage. However, the unconscious mind worry remains: What renders unconscious phenomena mental? I suggest a new strategy for answering this question, which rests on the idea that categorizing unconscious phenomena as "mental" should be scientifically useful relative to the explanatory research goals. I argue that this is the case if by categorizing an unconscious phenomenon as "mental" one picks out explanatorily relevant similarities to a corresponding paradigmatically mental conscious phenomenon. Explanatory relevance is spelled out in terms of mechanistic norms.